The Influence of Village Financial Management on Community Welfare. Case Study in Greneng Village, East Sakra District, East Lombok Regency - Sulman Hadi; Yousf Bellin Swarli (Saniya Institute, 2024)
The aim of this research is to see the influence of Village Financial Management (X) on the welfare of the Greneng Village Community, East Sakra District, East Lombok Regency. The sample used in this research was 30 respondents. The data analysis method used was simple linear regression including prerequisite assumption tests. Based on the results of the regression test, it was found that Village Financial Management (X) had a significant effect on the Welfare of the Greneng Village Community, East Sakra District, East Lombok Regency (Y). This is proven by a sig value of 0.000 < 0.05 in a positive direction. The Village Financial Management Variable (X) influences Community Welfare (Y) by 39.8%, while 60.2% is influenced by variables outside of observation.